Transient expression of intron-containing transgenes generates non-spliced aberrant pre-mRNAs that are processed into siRNAs - Dalakouras, Athanasios; Wassenegger, Michael (Planta, 2019)
Main conclusionIn this study, we show that aberrant pre-mRNAs from non-spliced and non-polyadenylated intron-containing transgenes are channelled to the RNA silencing pathway.In plants, improperly processed transcripts are called aberrant RNAs (ab-RNAs) and are eliminated by either RNA silencing or RNA decay mechanisms. Ab-RNAs transcribed from intronless genes are copied by RNA-directed RNA polymerases (RDRs) into double-stranded RNAs which are subsequently cleaved by DICER-LIKE endonucleases into small RNAs (sRNAs). In contrast, ab-RNAs from intron-containing genes are suggested to be channelled post-splicing to exonucleolytic degradation. Yet, it is not clear how non-spliced aberrant pre-mRNAs are eliminated. We reasoned that transient expression of agroinfiltrated intron-containing transgenes in Nicotiana benthamiana would allow us to study the steady-state levels of non-spliced pre-mRNAs. SRNA deep sequencing of the agroinfiltrated transgenes revealed the presence of sRNAs mapping to the entire non-spliced pre-mRNA suggesting that RDRs (most likely RDR6) processed aberrant non-spliced pre-mRNAs. Primary and secondary sRNAs with lengths of 18-25 nucleotides (nt) were detected, with the most prominent sRNA size class of 22 nt. SRNAs also mapped to the terminator sequence, indicating that RDR substrates also comprised read-through transcripts devoid of polyadenylation tail. Importantly, the occurring sRNAs efficiently targeted cognate mRNA for degradation but failed to cleave the non-spliced pre-mRNA, corroborating the notion that sRNAs are not triggering RNA cleavage in the nucleus.